Desenvolvimento de biossensores eletroquímicos baseados em acetilcolinesterase visando identificar extratos e substâncias para o controle de formigas cortadeiras - Araújo, Sean dos Santos (2019)
Brazil, which is a continental country, has an appropriate climate for various agricultural practices. Insects, in general, are considered pests for agricultural areas, among them, an Atta sexdens rubropilosa (leafcutter ant) that attacks as eucalyptus, pine plantations among others. Control of this pest becomes essential for the best productivity of cultivated areas. This control can be directed to inhibition of enzymes present in the target insect organism. In this line, the present work aims to immobilize the enzyme acetylcholinesterase (AChE) in SPEs (screen printed electrode), using the layer-by-layer technique, using AuNPs-GSH (glutathione-decorated gold nanoparticles) and EDC reagents ( 1-ethyl-3- (3-dimethylaminopropyl) carbodiimide) and HOBt (Hydroxybenzotriazole) which establish the covalent bonds responsible for immobilizing an AchE in the SPEs. Electrochemical responses confirm effective immobilization of the enzyme with this developed protocol. For inhibition assays, Azadiractin limonoid, Toona ciliata crude extract and Picramnia riedelli and P. ciliata crude extracts showed significant inhibition percentage against AChE. The 1H NMR spectra of the crude extracts used were obtained to propose natural compounds present in them and to indicate possible relationships with the results of the enzymatic assays. These extracts showed good insecticidal activity against the leafcutter ant.